Avaliação da cidadania participativa no PRODETUR/NE-II: o caso do Conselho de Turismo do pólo Costa das Dunas - Alves, Gilson Fernando (2009)
Participative citizenship is an investigation subject under the Dunes Coast Tourism Council, a public tripartite environment of discussion and deliberation which is part of the institutional structure of Northeast’s Tourism Development Program - Prodetur/NE, in its second phase. Through a study case methodology, there has been made an exploratory research that, in the attempt to understand how communitarian participation is built in that space and in which way it is influenced by the limits and potentialities of Prodetur/NE, it has relied on the hypothesis that, in the context of local tourism development, social capital is essential and determining the direction and the definition of this, especially with the use of all resources as endogenous factor of competitiveness of tourist destination. Accordingly, it is understood that the more consistent the social capital, the better the results achieved in the institutions of representation, and therefore will be more effective citizenship participation. A revealed confirmation as from the result’s analysis of the opinions expressed by 74 interviewed people, from different segments and representatives of the Dunes Coast Tourism Council. Based on these answers, it has been concluded that the Council’s space can be revealed inclusive and participative, if its weaknesses are worked out and its social capital is strengthened as from the divulgation, training (also for the council’s members) and development of local integrator spaces, that potentizes a participant citizen in the inner individuals.